Influence of sowing dates and nitrogen scheduling on growth behaviour and productivity of late sown wheat (Triticum aestivum L.) in north Indian plains - Kumar, Deepak; Singh, R.A.; Singh, Y. (Annals of Agricultural Research, 2016)
A field investigation was conducted during Rabi 2008–09 and 2009–10 to study the response of sowing time and nitrogen scheduling in wheat (Triticum aestivum L.) on its growth and yield under late sown conditions at Faizabad (UP). The treatments comprised of three sowing dates [5th , 15th and 25th December] and six nitrogen (N) schedules [N0 (control); N1 kg N at first irrigation; N2 – 50 kg N at sowing time + 50 kg N at first irrigation + 50 kg N at anthesis; N3 – 37.5 kg N at sowing time + 75 kg N at first irrigation + 37.50 kg N at anthesis; N4 – 50 kg N at sowing time + 50 kg N at first irrigation + 50 kg N at IInd irrigation; N5 sowing time] replicated four times in split plot design. Both sowing dates and N schedules significantly affected the initial plant population, plant height, number of shoots m–2, number of spikelets per spike, 1000–grain weight and grain and straw yields. In case of sowing dates, significantly maximum grain yield (32.6 and 33.4 q ha–1) was obtained where sowing of wheat was done on 5th December. Among N schedules, N3 gave significantly maximum yield (35.6 and 37.4 q ha–1) during both the years. – 75 kg N at sowing time + 75 – 100% N as basal dose at